تقويم كتاب اللغة العربية للصف الرابع الابتدائي (KSSR) بالمدارس الابتدائية في منطقة جوهر بهارو من وجهة نظر المعلمين - Ahmad Ghufran bin Mhd Rusdi (Kulliyah of Education, International Islamic University Malaysia, 2016)
The purpose of this study is to evaluate the primary four Arabic textbook from teachers' perspectives. The study which was conducted to teachers in Johor Bahru aims to investigate the textbook used in order to improve and upgrade the level of teaching Arabic as a second language. This is the first book for the second phase in teaching Arabic language in Malaysia. The researcher used the descriptive approach in data collection and analysis. A set of questionnaire was used to know the views of teachers in terms of the content of the book, activities, the layout and graphic of the textbook. The research sample consisted of 116 teachers. The study discovered that the teachers expressed their approval that textbook meets the requirements of the quality standards of textbook set by the experts in teaching of Arabic to non-native speakers. Of the three areas of quality textbooks, teachers agreed most to the contents of the textbook followed by layout and graphics, and activities.